2015
DOI: 10.1111/jphp.12378
|View full text |Cite
|
Sign up to set email alerts
|

Crystal forms of the hydrogen oxalate salt of o-desmethylvenlafaxine†

Abstract: Comparative solubility tests on ODV-OX Form 1 and o-desmethylvenlafaxine succinate evidenced a significant increase in solubility for the hydrogen oxalate salt (142 g/l) with respect to the succinate salt (70 g/l).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Many different approaches exist which all aim at generating different processing pathways for finding new polymorphs. Bulk crystallization experiments employ seeding, different solvents, ,, degree of saturation, and varying temperature, among others, to enable the production of new polymorphs which in other terms just represent the fact that the energy landscape is screened . Even the usage of structure prediction methods is becoming more important as potential new polymorphs might be more easily accessible in-silico but with the prediction rate exhausting physical capabilities. , …”
Section: Introductionmentioning
confidence: 99%
“…Many different approaches exist which all aim at generating different processing pathways for finding new polymorphs. Bulk crystallization experiments employ seeding, different solvents, ,, degree of saturation, and varying temperature, among others, to enable the production of new polymorphs which in other terms just represent the fact that the energy landscape is screened . Even the usage of structure prediction methods is becoming more important as potential new polymorphs might be more easily accessible in-silico but with the prediction rate exhausting physical capabilities. , …”
Section: Introductionmentioning
confidence: 99%
“…In the pharmaceutical industry, the polymorphic form of a drug shall be easily produced, compatible with the excipients used in the drug product manufacturing process, and remain unchanged for the duration of the drug’s shelf life. Consequently, many designs of experiments and screening methods are applied to generate potentially the best-suited approaches and stable polymorphs. In bulk crystallization experiments, various strategies are employed, including different solvents, , seeding, degrees of saturation, varying temperature, process parameter variation, and so on. We report for the first time in psilocybin synthesis a metastable crystallization zone and a drying process that produces a single stable anhydrous polymorphic form.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, two polymorphic forms were described, and the crystal structure resolution of Form B showed that it contained hydrogen oxalate anions [4]. In spite of the low incidence of oxalic acid in the list of the most used anions in APIs [5], many other examples have also been described in the literature exhibiting the interest of the scientific community for this coformer [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%